Morpho-anatomical features of the leaves and stems of Baccharis notosergila (Asteraceae) and their relationship with the environment and chemical control - Alejandra V. Carbone (Sociedad Argentina de Botánica, 2021)
Background and aims: Baccharis notosergila is an aggressive weed inhabiting the Salado river basin, Buenos Aires province, Argentina. The aims of this work were: to analyze the morpho-anatomy and histochemistry of aerial vegetative organs in order to understand the adaptation strategies that ensure its survival, as well as to expand knowledge on traits determining resistance to the control methods applied.